Economic and environmental life cycle assessment of alternative mass timber walls to evaluate circular economy in building: MCDM method - Ali Tighnavard Balasbaneh, Ali Tighnavard Balasbaneh; Willy Sher, Willy Sher (Springer, 2022)
The construction industry is one of the largest consumers of energy and materials, which leads to it being one of the highest sources of environmental emissions. Quantifying the impact of building materials is critical if strategies for mitigating environmental deterioration are to be developed. The lifecycle assessment (LCA) consequential methodology has been applied to evaluate diferent methods of constructing residential double-story buildings. The ReCiPe methodology has been used for life cycle inventory. Three diferent forms of mass timber construction have been considered including cross-laminated timber (CLT), nail-laminated timber (NLT), and dowel-laminated timber (DLT). These have been assessed as load-bearing panels or wood frame construction. We evaluated the global warming potential (GWP), embodied energy, and cost to identify the building type with the lowest impacts. The results revealed that total CO2 emissions for mass timbers for the construction stage are 130 CO2/M2 , 118 CO2/M2 , and 132 CO2/M2 of the panel for CLT, DLT, and NLT, respectively. The embodied energy emission is 1921 MJ/M2 , 1902 MJ/ M2 , and 2130 MJ/M2 related to the CLT, DLT, and NLT, respectively, for this stage. The results also indicated that the carbon emission of DLT is lowest compared to the other two alternatives in the manufacturing and construction stages. However, when the entire life cycle is considered, NLT is the most favorable material. However, based on the life cycle cost (LCC), DLT has a lower cost. Finally, multiple-criteria decision-making (MCDM) was used to normalize the results and compare the alternatives. This showed DLT to be the best alternative, followed by CLT and NLT. In conclusion, the selection of building materials needs to prioritize regulations to reduce environmental and economic impacts.